2023
DOI: 10.3390/catal13081180
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Roles of Cu/Ba on Ce-Based Passive NOx Adsorbers

Abstract: At present, passive NOx adsorbers (PNAs) represent one of the most effective technologies for addressing NOx emissions from diesel engines during cold-start periods. Conventional PNAs, which primarily consist of noble metals (such as Pt, Pd, and Ag) loaded on metal oxides or zeolites, share the common drawback of high production costs. Consequently, developing low-cost PNAs with outstanding NOx storage performance remains a significant challenge. In this study, a series of CuxBa5Ce adsorbents were synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Therefore, the XRD results showed that no significant differences were observed before and after the addition of Rh. In agreement with the previous report, 25 UV−vis DRs absorption bands belonging to (Cu−O−Cu) 2+ clusters were clearly observed at 430 nm from Cu5Ba5Ce, as shown in Figure 2b. It is worth noting that a significant red shift of the absorption band and a gradual shift to a broader shoulder peak could be observed after the loading of Rh, which have been due to the fact that the introduction of Rh promoted the concentration of Cu 2+ , thereby increasing the number of (Cu− O−Cu) 2+ clusters.…”
Section: Structural and Texturalsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the XRD results showed that no significant differences were observed before and after the addition of Rh. In agreement with the previous report, 25 UV−vis DRs absorption bands belonging to (Cu−O−Cu) 2+ clusters were clearly observed at 430 nm from Cu5Ba5Ce, as shown in Figure 2b. It is worth noting that a significant red shift of the absorption band and a gradual shift to a broader shoulder peak could be observed after the loading of Rh, which have been due to the fact that the introduction of Rh promoted the concentration of Cu 2+ , thereby increasing the number of (Cu− O−Cu) 2+ clusters.…”
Section: Structural and Texturalsupporting
confidence: 92%
“…As shown in Figure a, the main X-ray diffraction (XRD) diffraction peaks were assigned to the fluorite cubic structure of CeO 2 on both catalysts. Based on the previous work, the diffraction peak attributed to “LT-BaCO 3 ” (2θ = 23.9°) with excellent NO x storage performance was observed on both catalysts. No diffraction peaks associated with the Cu and Rh phases were observed.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…58 Pei et al showed that surface adsorbed oxygen acted as reactive oxygen and favored the formation of nitrogen dioxide to promote catalytic activity. 59 The O α significantly assisted in the increase in S–Ce activity. After sulfating H–Ce, the proportion of the O α /(O α + O β ) ratio of the H–S–Ce catalyst was greater compared to that of H–Ce.…”
Section: Resultsmentioning
confidence: 98%